Mulher de letras em relicário de papéis: itinerário de Zalina Rolim na imprensa periódica entre os séculos XIX e XX - Oliveira, Valnikson Viana de (2021)
The present work aims to investigate the participation of the writer Zalina Rolim (1867-1961) in the Brazilian periodical press between the end of the 19th century and the beginning of the 20th century, trying to reframe her name and her trajectory of erasure in literary historiography. The research defends the thesis that, in the bibliographical trajectory of the referred writer, more than the publication in a book, the participation in the periodical press allows the understanding of her inclusion in the intellectual field of her time. In this sense, we argue that the presence in prints of general interest, vehicles written by women and pedagogical journals was decisive in her path in literature. Thus, at first, we proposed to study and reflect on the activity of elite women in the historical-social and cultural context of that period, emphasizing the female conquest of public spaces through the word, showing how access to reading and writing enabled new perspectives on the pre-established female roles of mother, wife and “angel of the house”. For this, we used Bourdieu (2018), D'Incao (2018), Eleutério (2005), Lacerda (2003), Lajolo and Zilberman (1996), Louro (2018), Muzart (1999; 2000; 2003; 2011), Perrot (1992, 1998; 2005; 2019), Telles (2012; 2018), among others. With that, in a second moment, we were able to revisit and rewrite Rolim's biobibliographic trajectory from the periodicals, evaluating her social place and her intellectual sociability networks (SIRINELLI, 2003), identifying the possible production conditions offered to her writing through newspapers, magazines and almanacs in which she collaborated and the voices that reverberated and/or gave opinions about her production. To this end, we prioritize the search for primary sources, allowing to understand and reconstitute in a more credible and non-anachronistic way the literary life and the ways of appropriation of the written culture in the studied period (BARBOSA, 2007). In this way, we confirm or refute what is mentioned in the main researches on the life and work of the studied author, such as Piza (2008) and Dantas (1983), also being able to identify the difference in treatment between the criticism made by men and criticism made by other women about the work of the studied author. Finally, we also intend to measure the scope of the studied author's production by locating reproductions or republications of her writings in journals that did not receive her effective collaboration. The survey of collaborations in the press follows the transformations in Rolim's creative production over the years and presents her work to new readers, resizing her place in literary studies conducted between the 19th and 20th centuries.